Sherlock Holmes in : - Doyle, Arthur Conan (The english bookmarks)
Our proceedings of that first morning did little lo advance the investigation. It was marked, however, al the outset by an incident which left the most sinister impression upon my mind. Theapproach to the spot at which the tragedy occurred Is down a narrow, winding, country lañe. While we made our way along it we heard therattle ofa carriage comlng towards usandstood aside to letit pass. As it drove by us Icaught aglimpse through the closed window of a horribly contorted, grinning face glaring out at us. Those staring eyes and gnashing teeih flashed past us like a dreadful visión.